AKTIVITAS SITOTOKSIK ISOLAT 5 FRAKSI ETIL ASETAT EKSTRAK PETROLEUM ETER DAUN Phaleria macrocarpa (Scheff.) Boerl. PADA TURUNAN SEL KANKER SERVIKS MANUSIA (HeLa) - Utami, Dwi (Pharmaciana, 2011)
Cervical cancer is a malignant tumor in cervix which is occupy the secondpossition that cause the death of Indonesiaâs women under the breast cancer. One of thetraditional medicine that can be used to cure cancer is Phaleria macrocarpa(Scheff.) Boerl leaves. The petroleum eter extract of Phaleria macrocarpa(Scheff.) Boerl leaves has antiproliferation activity againts cervical cancer cell lines(HeLa) with IC50 9 Âµg/ml (Kintoko & Azimahtol Hawariah, 2007). This research wasaimed to detect cytotoxic activity of isolate 5 of ethyl acetate fraction of petroleum etherextract of Phaleria macrocarpa (Scheff.) Boerl leaves againts HeLa cell lines. Initially,the powder of Phaleria macrocarpa (Scheff.) Boerl was extracted using Soxhletapparatus with petroleum ether. The extracts was concentrated and partitioned untilethyl acetate fraction was obtained. The fraction of ethyl acetate was isolated usingPreparative Thin Layer Chromatography on silica gel F254 as stationary phase andn-hexane : ethyl acetate (9 : 1) as mobile phase. Cytotoxic activity against HeLa celllines was determinated by LC50 value by direct counting. The isolation by preparativethin layer chromatography resulted five isolate on Rf value : 0,05 ; 0,10 ; 0,20 ; 0,60 ;and 0,90. The LC50 values of isolate 5 (Rf : 0,90) was 123,60 Âµg/ml.